Upaya Pencegahan Penularan Covid-19 Pada Anak Usia Dini Di Tpq Darussalam Dusun Sukorejo Desa Kepung Kecamatan Kepung Kabupaten Kediri - Rika Asmarani; Khoiruzzaim Kurniawan (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
This study includes how to prevent the transmission of COVID-19 in early childhood in TPQ Darussalam, Kepung Village. Effort has the meaning of effort or determination to achieve something desired. While prevention is anticipating something that might happen. So the effort to prevent transmission is an effort to anticipate the spread of COVID-19 which is currently rife throughout the world. Efforts that can be made include washing hands, wearing masks, maintaining distance, exercising, and cleaning the environment. The efforts that are being made are not only outwardly but also mentally, they also need to be done, such as praying for the end of the current pandemic.